Cekaman Garam NaCl danTeknik Aplikasi Azolla pada Tanaman Padi - Fitri Krismiratsih; Sugeng Winarso; Slamerto Slamerto (Institut Pertanian Bogor, 2020)
Efforts to increase production potential can be carried out by extensification in a less productive saline land. Salinity is a major problem in the growth of most plants. Azolla is a plant that is sensitive to salinity, but if it is applied well, it can grow optimally at high salinity levels. The purpose of this study is to obtain an azolla application technique that is effective in increasing the adaptation of rice plants to NaCl saline soil conditions. The experimental design used was Randomized Block Design (RBD) with 2 factors and 3 replications. The first factor was the azolla application technique consisted of 3 levels: fresh azolla composted, fresh azolla immersed, and fresh azolla as a ground cover. The second factor was the levels of NaCl salt stress consisted of 4 levels: control DHL 0, 2, 4, and 8 dS m-1. The adaptation ability of rice plants based on variable plants height growth rate, number of tillers, strove dry weight, root dry weight, stomata density, leaf chlorophyll (SPAD), age of flowering, number of paddy grain, and harvest index. The results showed how to test content up to 2 dS m-1 which increased rice growth especially the application of azolla composted. Increasing stress to 4 and 8 dS m-1showed bad effects on vegetative, physiology, and yields of rice components. The stronger of salt stress the higher all plants growth variables except the age of flowering that actually showed the acceleration of flowering. Application of composted azolla can increase the root dry weight and azolla as a ground cover can increase the numbers of paddy grains. Keywords: azolla, NaCl, rice, stress